Participatory modelling with an influence matrix and the calculation of whole-of-system sustainability values. (23rd April 2008) - Cole, Anthony; Allen, Will; Kilvington, Margaret; Fenemor, Andrew; , Breck Bowden
This paper documents the results of a participatory modelling trial involving an influence matrix with a group of researchers and community members in the Motueka Catchment of New Zealand. In this trail, the influence matrix was used to calculate whole-of-system sustainability-values used to: (i) guide system dynamic model development, (ii) build understanding about the functional role of system factors, and (iii) contribute to method and theory development in a sustainability research context. This paper provides: (i) an historical account of the theoretical development of the influence matrix, (ii) theoretical justification for the use of this tool in the estimation of whole-of-system sustainability values, and (iii) a stepwise account of how the method has been trialled in a New Zealand case study, including an evaluation of its limitations and areas where future research is needed.